2020
DOI: 10.1016/j.drugalcdep.2019.107676
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with subsequent initiation of cigarettes and e-cigarettes in adolescence: A structural equation modeling approach

Abstract: Background-Previous youth tobacco research has identified multiple correlated risk factors for initiation of cigarette and e-cigarette use; whether these factors are independently associated with initiation is not known, due to challenges with disentangling the independent effects of these correlated risk factors.Methods-Students in 11 th /12 th grade enrolled in the Southern California Children's Health Study were surveyed in 2014 (baseline) and again in 2015 (N=1553). Structural equation models (SEM) were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
2
12
0
5
Order By: Relevance
“…The importance of our findings should be considered because while e-cigarettes have been marketed as a cessation tool, our findings show that e-cigarettes may predispose young adults to initiate cigarette use at earlier ages than never e-cigarette users. Similarly, our results are consistent with research that has found that previous use of other tobacco products is associated with subsequent cigarette use in adults [11], college students [56,57], and youth [58][59][60]. Our study again extends these findings specifically to young adults.…”
Section: Plos Onesupporting
confidence: 91%
“…The importance of our findings should be considered because while e-cigarettes have been marketed as a cessation tool, our findings show that e-cigarettes may predispose young adults to initiate cigarette use at earlier ages than never e-cigarette users. Similarly, our results are consistent with research that has found that previous use of other tobacco products is associated with subsequent cigarette use in adults [11], college students [56,57], and youth [58][59][60]. Our study again extends these findings specifically to young adults.…”
Section: Plos Onesupporting
confidence: 91%
“…O tempo de seguimento dos estudos variou entre 6 meses e 2 anos e 80% (n=20) deles incluiu, adolescentes e estudantes do ensino médio. O desfecho foi considerado como, pelo menos, a experimentação de cigarro convencional (1 ou 2 tragos) em 22 estudos [14][15][16][17][18][19][21][22][23][24][25][26][27][28][29][30][32][33][34][35][36][37] e o seu uso atual (nos últimos 30 dias) em 9 estudos [13][14][15]20,25,[30][31][32]37 . O risco geral de viés avaliado pela ferramenta ROBINS-I foi moderado ou baixo para a maioria dos estudos (Quadro 1).…”
Section: Resultsunclassified
“…Toutefois, chez les élèves de sexe féminin, le fait de respecter les directives sur le temps passé devant un écran au début de l'étude et au moment du suivi (soit la catégorie « usage constant ») était associé de façon négative à l'initiation à la cigarette électronique. Des recherches antérieures ont établi un lien entre l'exposition à la publicité sur la cigarette électronique et l'initiation à la cigarette électronique 9,17,18 , et les élèves qui respectent les recommandations canadiennes sur le temps passé devant un écran pourraient être moins exposés à la publicité, particulièrement en ligne. La promotion de la cigarette électronique est répandue en ligne, et les jeunes qui déclarent y avoir été exposés sont plus susceptibles de commencer à l'utiliser 47,48…”
Section: Analyseunclassified
“…Selon les données dont on dispose, plusieurs facteurs sont associés à l'initiation à la cigarette électronique : le tabagisme (p. ex. cigares, cigarillos) et la consommation de substances [9][10][11][12] , une forte tendance à rechercher des sensations 13,14 , une mauvaise santé mentale 15,16 , l'exposition à la promotion de la cigarette électronique 9,17,18 et des attitudes positives à l'égard des cigarettes électroniques chez la personne, les amis et la famille 9,[19][20][21] . Bien que de nombreuses études aient établi une association significative entre l'initiation à la cigarette électronique et le genre, ces études n'ont pas exploré de quelle façon les facteurs prédictifs pouvaient différer selon le genre 9,10,[13][14][15]18,19…”
Section: Introductionunclassified